Control interno de las cuentas - documentos por cobrar y por pagar y su incidencia en la liquidez de la piladora San Agustín cantón Babahoyo, período 2017-2018 - Jiménez García, Luis Fernando (2018)
The research project was carried out at the San Agustín Battery, located in the Babahoyo Canton, where an internal control was applied to the administrative and financial processes, where a reasonable degree of security was achieved, taking as a reference the effectiveness and efficiency of the operations, reliability of financial information and compliance with laws, regulations and norms that are applicable. One of the main items considered in a company is the availability of cash with which it has to manage the different negotiations within the market, it is for this reason that a study was required to the accounting accounts that have an impact on profitability and productivity in terms of the economic turn of the business, thus strengthening the financial information that is granted to shareholders for management decision making. An internal control was developed in the San Agustín Battery, in the management of the accounts documents receivable and paid and their incidence in the liquidity of the same, since deficiencies in the recovery management of the accounts and documents were evidenced receivable, as well as timely cancellation of accounts documents payable by the company to invest in the cultivation and harvest of rice. Information was obtained through research techniques such as the interview and survey, and internal control matrices were used to serve as the basis for the development of this evaluation and thus determine the risks that were faced, later financial reasons were used to measure the degree of average collection, indebtedness, liquidity and profitability that serve as a basis for examining the actual financial situation of the Piladora and evaluating the degree of recovery of the accounts and documents receivable from clients, in addition to the obligations contracted with financial entities. x KEYWORDS: Internal control, Liquidity, Accounts receivable, Documents payable, Profitability